2021
DOI: 10.7554/elife.67256
|View full text |Cite
|
Sign up to set email alerts
|

Rotational dynamics in motor cortex are consistent with a feedback controller

Abstract: Recent studies have identified rotational dynamics in motor cortex (MC), which many assume arise from intrinsic connections in MC. However, behavioral and neurophysiological studies suggest that MC behaves like a feedback controller where continuous sensory feedback and interactions with other brain areas contribute substantially to MC processing. We investigated these apparently conflicting theories by building recurrent neural networks that controlled a model arm and received sensory feedback from the limb. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
71
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(77 citation statements)
references
References 112 publications
(215 reference statements)
1
71
2
Order By: Relevance
“…Perhaps what appear to be “neural dynamics” merely reflect incoming sensory feedback mixed with outgoing commands. A purely feedforward network could convert the former into the latter, and might appear to have rich dynamics simply because the arm does (Kalidindi et al 2021). While plausible, this hypothesis strikes us as unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps what appear to be “neural dynamics” merely reflect incoming sensory feedback mixed with outgoing commands. A purely feedforward network could convert the former into the latter, and might appear to have rich dynamics simply because the arm does (Kalidindi et al 2021). While plausible, this hypothesis strikes us as unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…More generally, the presence of sensory feedback complicates the interpretation of apparent "dynamics" in motor cortex. For example, a recent study demonstrated that neural population activity in the somatosensory cortex (Kalidindi et al, 2021) possesses many features attributed to dynamics in M1, in particular, rotations in neural state space (Russo et al, 2018). For these reasons, it is difficult to say what proportion of the dynamical behavior that we see in M1 is due to its own dynamics, versus dynamics "inherited" from other areas, including sensory input.…”
Section: Motor-potent Spaces Translate Neural Dynamics Into Muscle Activitymentioning
confidence: 96%
“…The brain can adjust feedback gains according to planning and context, thereby altering the nature of the transformation of state estimates into motor output. Most research in this field has been at the level of movement psychophysics (Mazzoni & Krakauer, 2006;Sha et al, 2006;Taylor et al, 2014), only infrequently examining the firing rates of single neurons (Cross et al, 2021;Kalidindi et al, 2021;Pruszynski, 2014;Pruszynski et al, 2011). OFC presents what might be considered an "algorithm-level" description of how the motor system controls movements but is largely agnostic to how this algorithm is implemented by neurons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, a group of researchers discovered that when they trained a recurrent artificial network to generate the motor activities needed for movement, the patterns resembled the rotational activity seen in the motor cortex ( Sussillo et al, 2015 ). Now, in eLife, Hari Teja Kalidindi (Scuola Superiore Sant'Anna), Kevin P Cross (Queen's University) and colleagues report that it is also possible to train a neural network to control an artificial arm without using any recurrent connections inside the network ( Kalidindi et al, 2021 ).…”
mentioning
confidence: 99%